The Effect of Different Parameters on Shape Memory Alloys - Qader, İbrahim Nazem; Kök, Mediha; Dağdelen, Fethi; Abdullah, Shakhawan Salih (Sakarya University, 2020)
Shape memory alloys’ characteristics are different from ordinary materials because they can memorize their pre-determined shape, thus they are excellent candidates for different applications. In this review article, the most interesting parameters that researchers are using in their investigation have been highlighted. Also, the popular techniques used for the characterization of shape memory alloys have been described. The diagrams and sketches can show a clear view of metallurgies and related research areas. © 2020, Sakarya University. All rights reserved.
Keywords: characterization process; diagrams; Shape memory alloys; sketches